Association between plasma selenium and risk of ischemic stroke: A community-based, nested, and case-control study - Wang, Zhuo; Hu, Shiyu; Song, Yun; Liu, Lishun; Huang, Zhengzheng; Zhou, Ziyi; Wei, Yaping; Lin, Tengfei; Huang, Meiqing; Zhang, Hao; Guo, Huiyuan; Sun, Yong; et al. (Frontiers in Nutrition, 2022)
Background: The prospective association between plasma Se and stroke risk remains inconclusive. The relation of Se and ischemic stroke among a low circulating Se status population deserves more attention, especially for Chinese were a high-risk group in Se deficient. Objective: The relationship between plasma Se concentration and ischemic stroke risk in a large-scale Chinese community-based population and any potential effect modifiers were investigated. Methods: A nested, case-control study, using data from the ‘China H-type Hypertension Registry Study’ were conducted. A total of 1904 first ischemic stroke cases and 1904 controls matched for age, sex and village were included in this study. Association between plasma Se and first ischemic stroke were evaluated by conditional logistic regression analyses. Results: The median value of plasma Se was 65.8 μg/L among total participants. Overall, a significant inverse relationship between plasma Se and first ischemic stroke risk was found (per SD increment; adjusted OR: 0.87; 95% CI: 0.80, 0.95). Accordingly, a significantly lower risk of first ischemic stroke was found in participants in quartile 3 (65.8-<77.8 μg/L) (adjusted OR: 0.78; 95% CI: 0.63, 0.96) and quartile 4 (≥77.8 μg/L) (adjusted OR: 0.76; 95% CI: 0.59, 0.96), compared with those in quartile 1 (<56.0 μg/L). Furthermore, a significantly lower ischemic stroke risk was found in those with lower low-density lipoprotein cholesterol (LDL-C) levels (< 3.4 versus ≥3.4 mmol/L; P for interaction = 0.015) or those with lower homocysteine levels (< 12.1 (median) versus ≥12.1 μmol/L; P for interaction = 0.027) at baseline. Conclusions: Plasma Se was significantly inversely associated with risk of first ischemic stroke among a large-scale Chinese community-based population (most of adults with hypertension and elevated total homocysteine), especially among those with lower LDL-C and lower homocysteine levels.